A novel histological index for evaluation of environmental enteric dysfunction identifies geographic-specific features of enteropathy among children with suboptimal growth - Liu, Ta-Chiang; VanBuskirk, Kelley; Ali, Syed A.; Kelly, M. Paul; Holtz, Lori R.; Yilmaz, Omer H.; Sadiq, Kamran; Iqbal, Najeeha; Amadi, Beatrice; Syed, Sana; Ahmed, Tahmeed; Moore, Sean; et al. (PLOS Neglected Tropical Diseases, 2020)
Author summary The study of EED has been limited by the lack of a rigorously tested, reproducible histology index that can provide insight to the pathogenesis of this entity. In this study we report the first duodenal histology index that was developed using an unbiased approach, with excellent inter-observer reproducibility, for the study of EED. The EED histology index readily identified histologic features that are common or unique to cohorts of distinct geographic locations. Incorporating the histology index into future clinical studies will provide useful insight into the pathogenesis and for intervention strategy development.